Acceptance of Mobile JKN Application Technology Among Older Adults Reviewed from the Technology Acceptance Model in Supporting Gerontic Nursing Services - Crisna Lumban Gaol; Jefry Banjarnahor; Mery Lestari Simanjuntak; Dewi Purba; Renta Sihombing (Sean Institute, 2025)
The Mobile JKN application is a digital service innovation developed by BPJS Kesehatan to facilitate public access to healthcare services online. Among the elderly, technology acceptance becomes a challenge due to age limitations, technological abilities, and adaptation to digital systems. This study aimed to analyze the technology acceptance of the Mobile JKN application among the elderly based on the Technology Acceptance Model (TAM) in supporting gerontic nursing services in Humbang Hasundutan Regency in 2025. This research used a quantitative method with a cross sectional design. The population consisted of elderly users of the Mobile JKN application in Humbang Hasundutan Regency. The sampling technique used purposive sampling with a total sample of 379 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results showed that perceived usefulness significantly affected elderly user satisfaction with a p-value of 0.000 and t-statistic of 13.547. Perceived ease of use significantly affected elderly user satisfaction with a p-value of 0.000 and t-statistic of 4.828. Perceived usefulness significantly affected continuance intention to use the Mobile JKN application with a p-value of 0.000 and t-statistic of 7.034. Perceived ease of use also significantly affected continuance intention with a p-value of 0.000 and t-statistic of 4.483. Elderly user satisfaction significantly affected continuance intention with a p-value of 0.03 and t-statistic of 2.177. Based on the results, it can be concluded that the technology acceptance of the Mobile JKN application among the elderly is influenced by perceived usefulness and perceived ease of use in supporting gerontic nursing services in Humbang Hasundutan Regency in 2025.